Effect of calcium hydroxide and adipose-derived stem cell conditioned medium (ADSCs-CM) combination on reparative dentin formation in Wistar rats through RUNX-2 and OPN expression - Radixtio Auzan Fepiosandi; Dian Agustin Wahjuningrum; Galih Sampoerno; Anuj Bhardwaj; Ajinkya M. Pawar (Journal of Oral Biology and Craniofacial Research)
Background: Vital pulp exposure requires effective pulp capping to preserve the vitality and function of the dental pulp. Calcium hydroxide (Ca(OH)2) is widely used as a pulp capping agent; however, it has significant limitations, including the formation of reparative dentin with tunnel defects. These defects may compromise long-term success. Adipose-derived stem cell conditioned medium (ADSCs-CM) has shown regenerative potential through paracrine mechanisms. Objectives: To evaluate the effect of combining Ca(OH)2 with ADSCs-CM on the expression of odontogenic markers RUNX-2 and osteopontin (OPN), and secondarily to assess the histological characteristics of reparative dentin in healthy Wistar rats. Materials and methods: An in vivo experimental study was conducted using twelve healthy female Wistar rats (Rattus norvegicus), randomly divided into control (Ca(OH)2 only) and treatment (Ca(OH)2 + ADSCs-CM in a 2:1 ratio) groups (n = 6/group). Class V cavities were prepared with standardized pulp exposure. Following hemostasis, the respective materials were applied and sealed with glass ionomer cement. Histological evaluation using hematoxylin and eosin (HE) staining and immunohistochemical assessment of RUNX-2 and OPN expression were performed on days 1, 3, and 6. Statistical analysis was conducted using the Shapiro-Wilk test and independent t-tests (p < 0.05). Results: RUNX-2 and OPN expressions were significantly higher in the treatment group at all time points (p < 0.05), with peak levels observed on day 6. Histologically, the treatment group exhibited more homogeneous and better organized reparative dentin compared to the control group. Conclusion: The addition of ADSCs-CM to Ca(OH)2 enhances reparative dentinogenesis by upregulating RUNX-2 and OPN expression. This combination therapy may serve as a biologically favorable alternative for direct pulp capping procedures.